Community Empowerment in Preventing and Overcoming Dengue Hemorrhagic Fever (DHF) with 3M Plus - Budi Yulianto; Budi Joko Santosa; Handoyo Handoyo; Nurlailis Saadah (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
The number of people suffering from Dengue Hemorrhagic Fever (DHF) in Magetan Regency from year to year shows a significant increase. Starting from 2021 to 2023, there are 5 sub-districts that have been declared endemic areas for dengue fever, including Ngariboyo Sub-district. Baleasri Village, Ngariboyo District, has many places where mosquitoes’ nest. There are still many people's houses that lack lighting and are damp, making them suitable places for mosquitoes to live. The aim of this Community Partnership Program (PKM) activity is to facilitate the community in preventing and controlling dengue fever independently so that their health level increases. The method used is a combination of Community Development and education models by empowering housewives, youth organizations, larva monitoring cadres (Jumantik), sanitation working group cadres (pokjasan) as subjects and objects. Implementation of activities takes the form of training and mentoring under the guidance of facilitators, health officers and support from the Village Head. The material includes the importance of eradicating mosquito nests (PSN) with 3M Plus for the prevention and eradication of dengue fever. The results achieved were increased community understanding and skills in preventing and eradicating dengue fever with PSN 3M Plus which was carried out by the community independently.